Eksplorasi Pengalaman Konsumen terhadap Pemasaran Digital melalui Media Sosial TikTok dalam Keputusan Pembelian Produk Kahf - Maliq Zahran Abhista; Dhandy Catur Maryono (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to explore consumer experiences with digital marketing through TikTok in influencing purchasing decisions of Kahf products. A qualitative approach with a phenomenological method was applied to understand consumers’ perceptions and subjective experiences. Data were collected through in-depth interviews with informants who had seen Kahf content on TikTok and made purchases, then analyzed using thematic analysis. The findings show that content appearing on the FYP plays a role in increasing consumer exposure. Appealing visuals, simple message delivery, and interaction with audiences enhance engagement. In addition, factors such as trends, virality, and trust in user reviews and influencers influence purchasing decisions, both rationally and impulsively. This study concludes that TikTok functions not only as a promotional medium but also as a source of information that shapes consumer perceptions and purchasing decisions.